1990
DOI: 10.1111/1467-9566.ep11347163
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of HIV‐related risk behaviour and risk reduction between female street working prostitutes and male rent boys in Glasgow

Abstract: In this paper we provide an early report of two continuing ethnographic studies of prostitution. We compare female streetworking prostitutes and male rent boys in Glasgow in terms of risks of HIV infection and practice of safer sex. It is shown that a considerable proportion of streetworking female prostitutes in Glasgow were injecting drug users but that drug use was much less common among rent boys. Although condom use appeared to be widespread amongst the women it was less common among the rent boys. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…This relative non-dependence on sex work may provide them some relative control in their sex work encounters, which is a key factor in whether sex workers can restrict the encounter to safe sex (Bloor et al, 1992;McKeganey et al, 1990;Simon et al, 1994). That they were more likely to use condoms in the context of sex work than during casual sex encounters indicates that they did not engage in sex work without some consideration of the potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…This relative non-dependence on sex work may provide them some relative control in their sex work encounters, which is a key factor in whether sex workers can restrict the encounter to safe sex (Bloor et al, 1992;McKeganey et al, 1990;Simon et al, 1994). That they were more likely to use condoms in the context of sex work than during casual sex encounters indicates that they did not engage in sex work without some consideration of the potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…This also supports our previous contention that efforts should be based on negotiations and decision-making skills and techniques to counterbalance sources of imbalance in the CSE. Several studies have found that safe sex is in most cases determined by the ability of the sex worker to gain control of the sexual encounter (Bloor et al ., 1992;McKeganey et al ., 1990;Simon et al ., 1993). This ability could be diminished with substance use (Graaf et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In this sub-group, hard drugs (heroine and cocaine) were also common, most of them being poly-drug users. Yet another study, in Glasgow, found that few MSWs, mostly street workers, were IV drug users (McKeganey et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…So Scambler and Scambler (1997) in their survey of sex work in the UK insist on a 'presumption of wilful rationality' and the 'respectful attribution of agency' in making sense of the behaviour of those who work in the sex industry. McKeganey et al (1990) have shown the importance of individual meaning-making, initiative and agency in regard to risk outcomes in studies of interactions between sex workers and their clients. Female sex workers on the streets de ned encounters with potential clients as business, and were explicit about price, service and condom use at the beginning of an encounter.…”
Section: Introductionmentioning
confidence: 99%